Effect of Harness Training With Swiss Ball Core Exercises Program on Throwing Accuracy among Men Basketball Players: The Impact of Harness Training and Swiss Ball Core Exercises on Throwing Accuracy among Men Basketball Players (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present study was undertaken to analyze the effect of harness training with core exercises program on throwing accuracy among men basketball players. The investigator has selected N=48 men inter collegiate levelstate level participated basketball players at random from various college of Nellore district of Andhra Pradesh .Their age ranged from 18-25 years. The basketball players chosen for the study were divided into four equal groups n=12 and designated as experimental group ‘A’ experimental group ‘B’ experimental group ‘C’ and control group ‘D’. Harness training were given to group ‘A’ Swiss ball core exercises training were given to group ‘B’, Combined training of harness training and Swiss ball core exercises training were given to group ‘C’ and the ‘CG’ control group ‘D’ were restricted to participate in any activities. The trainings were given for a period of twelve weeks. The data were collected before and after the training by conducting throwing accuracy test [Johnson basketball test]. The obtained data’s were analyzed by Analysis of Covariance (ANCOVA). The level of significant was fixed at 0.05 levels. The results of the study showed that Harness training, Swiss ball core exercises training and combined training significantly improved basketball throwing accuracy performance of the basketball players when comparative with control group. The Combined training group basketball players shown better performance in basketball throwing accuracy performance test when comparison with harness training group and Swiss ball core exercises training group basketball players.